2010
DOI: 10.1007/s00784-010-0419-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in burning mouth syndrome: a case–control study based on patient records

Abstract: Burning mouth syndrome (BMS) is a multifactorial condition which is still poorly understood. The aim of this study was to evaluate a group of patients with BMS, as compared to a control group, and to describe related local and systemic factors. Records of patients referred to the Oral Pathology Service at the School of Dentistry over a period of 7 years were considered for the study, within which 32 patients with a diagnosis of BMS were found. A randomized group matched for age and gender was also evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
3
42
0
5
Order By: Relevance
“…The epidemiology of BMS is imprecise in literature because of the wide range of definitions and diagnostic criteria. Most studies investigate the cause of oral burning pain rather than idiopathic BMS (3,4,14,15). The concept of a pragmatic approach in dividing BMS into primary (idiopathic) and secondary (with a known cause) was first introduced by Scala et al (11) and supported by others in the literature (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of BMS is imprecise in literature because of the wide range of definitions and diagnostic criteria. Most studies investigate the cause of oral burning pain rather than idiopathic BMS (3,4,14,15). The concept of a pragmatic approach in dividing BMS into primary (idiopathic) and secondary (with a known cause) was first introduced by Scala et al (11) and supported by others in the literature (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Burning mouth syndrome is typically described by the patient as burning, stinging and/or itching of the oral cavity in the absence of any organic disease. It lasts at least for 4-6 months duration and typically located on the tongue, particularly in the tip and lateral borders, lips, hard & soft palate, alveolar ridges with the buccal mucosa and floor of the mouth being less frequently involved [2][3][4][5] . BMS mainly affects middle aged or old women with hormonal changes or psychological disorders [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study found age-adjusted prevalence rates of 18.8 and 3.7 cases in women and men, respectively in 100,000 people 15 , while another investigation discovered that BMS occurs in 1 in every 1,000 subjects, mainly in women over 50 years old 16 . Also, the evaluation of 3,243 medical records found that 0.99% of patients could have BMS 17 . Women are the most affected group, usually at a 7 to 1 ratio against men, 90% of whom are in the perimenopausal stage.…”
Section: Bms Epidemiologymentioning
confidence: 99%
“…The burning sensation is felt in the morning, worsening progressively during the day and subsiding at night 3,11 . Risk factors include standing gastrointestinal or urogenital conditions 12,17 , mild neuropathy in small autonomic and sensory fibers, side effects of medical drugs, and former smoking habit 12 .…”
Section: Bms Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation